Togo - 2018: Domestic politics, foreign affairs, socio-economic development - Dirk Kohnert (Africa Yearbook Volume 15 - Politics, economy and society South of the Sahara in 2018, 2019)
Throughout the year the controversial legislative elections dominated the political landscape. Huge anti-government demonstrations that called in vain for political alternance. The legislative elections of 20 December 2018, boycotted by the major opposition parties, resulted in an easy victory of the ruling party, however without the expected constitutional amendment majority. Therefore, the prime minister and his cabinet were replaced. The local elections, crucial for democratization at the grassroots , but postponed time and again since 1987, were again postponed in December 2018 sine die. Economic growth remained stable at about 5% per annum. Public investment in infrastructure (e. g. roads, harbour) and increases in agricultural productivity, notably of export crops, had been the key drivers of economic growth. Moreover, money-laundering, illegal money transfers and trafficking grew alarmingly. Unemployment and lacking political change caused increasing migration. – – Tout au long de l'année, les élections législatives controversées ont dominé le paysage politique. D'énormes manifestations antigouvernementales réclamaient en vain une alternance politique. Les élections législatives du 20 décembre 2018, boycottées par les principaux partis de l'opposition, ont permis une victoire facile du parti au pouvoir, sans toutefois obtenir la majorité requise pour un amendement constitutionnel. Par conséquent, le premier ministre et son cabinet ont été remplacés. Les élections locales, cruciales pour la démocratisation à la base, mais reportées à plusieurs reprises depuis 1987, ont été à nouveau reportées en décembre 2018 sine die. La croissance économique est restée stable à environ 5% par an. Les investissements publics dans les infrastructures (routes, ports, etc.) et l'augmentation de la productivité agricole, notamment des cultures d'exportation, ont été les principaux moteurs de la croissance économique. En outre, le blanchiment d'argent, les transferts d'argent illégal et le trafic se sont multipliés de manière alarmante. Le chômage et l'absence de changement politique ont provoqué une migration croissante. – – Während des ganzen Jahres dominierten die umstrittenen Parlamentswahlen die politische Diskussion. Andauernde große Demonstrationen gegen die Regierung, forderten vergeblich einen Wechsel an der politischen Macht. Die Parlamentswahlen vom 20. Dezember 2018, die von den großen Oppositionsparteien boykottiert wurden, führten zum leichten Sieg der Regierungspartei, jedoch ohne die erwartete qualifizierte Mehrheit für eine Verfassungsänderung. Deshalb traten der Premierminister und sein Kabinett zurück. Die für die Demokratisierung an der Basis entscheidenden Kommunalwahlen, die seit 1987 immer wieder verschoben wurden, wurden im Dezember 2018 erneut auf unbestimmte Zeit verschoben. Das Wirtschaftswachstum blieb stabil bei etwa 5% pro Jahr. Öffentliche Investitionen in die Infrastruktur (z. B. Straßen, Häfen) und die Steigerung der landwirtschaftlichen Produktivität, insbesondere von Exportkulturen, waren die Haupttreiber des Wirtschaftswachstums. Darüber hinaus nahmen Geldwäsche, illegale Geldüberweisungen und Menschenhandel alarmierend zu. Arbeitslosigkeit und mangelnde politische Wende führten zu einer zunehmenden Migration.
Keywords: A14; F35; N97; O17; O55; Z13; 330; countrywide study; Togo; West Africa; domestic politics; foreign affairs; socio-economic development; ECOWAS; WAEMU